Perceived impacts of sex education as a preventive measure for STIs among youths in Lilongwe, Malawi - Mwanyimbo, Alfred E.; ADAMU, VE (Orapuh Journal, 2020)
Introduction STIs seem to be on the rise among men and women across the world and this is a worrisome development. World Health Organization (WHO) estimated that 1 million curable STIs occur each day globally. Purpose The purpose of this research was to assess the perceived impacts of sex education in the prevention of the further spread of Sexually Transmitted Infections (STIs), including Human Immunodeficiency Virus (HIV) among youths. Materials & methods Secondary data obtained from both search engines and a few health institutions in Malawi were used for the study. A few questionnaires were also administered to 10 healthcare workers to collect data on sex education and STIs. Results Findings suggest that sex education initiatives are available to the youth in Lilongwe, Malawi, but these initiatives are not adequate to prevent STIs among youths. Besides, youths experienced barriers related to service availability and accessibility, and also lacked access to integrated sex education services. Youths reported avoiding services or having confidentiality concerns based on provider demographics and some behaviors. Finally, this study suggested that sex education can be one of the vital tools in the prevention of the further spread of STIs, including HIV if adequately engaged. Conclusions Sex education programs are available in Malawi and they are the most preferred services when it comes to sexual behavior change. Efforts need to be mustered to improve or increase sex education initiatives and promote their satisfactory uptake.